1998
DOI: 10.1016/s0194-5998(98)70063-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide is a Regulator of Mucociliary Activity in the Upper Respiratory Tract

Abstract: The in vitro effects of the nitric oxide (NO) substrate L-arginine on ciliary beat frequency and the in vivo effects of the NO donor sodium nitroprusside (SNP) on mucociliary activity were investigated in the rabbit maxillary sinus mucosa with photoelectric techniques. L-Arginine increased ciliary beat frequency in vitro with a maximum response of 27.1% +/- 6.4% at 10(-3) mol/L, and this effect was reversibly blocked by pretreatment with the NO synthase (NOS) inhibitor N(G)-nitro-L-arginine, whereas D-arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…NO is part of the first-line host defense mechanisms; its high concentration in the paranasal sinuses can reach up to 23.000 ppb [10], ensuring an antibacterial, antiviral, and antifungal effect. NO increases mucociliary clearance by upregulating ciliary motility; an association between low levels of NO and impaired mucociliary transport has been established [23,24]. Importantly, nitric oxide can display a pro- or anti-inflammatory effect conditioned by the type and phase of airway inflammation, its local concentration, and the individual response [25].…”
Section: Discussionmentioning
confidence: 99%
“…NO is part of the first-line host defense mechanisms; its high concentration in the paranasal sinuses can reach up to 23.000 ppb [10], ensuring an antibacterial, antiviral, and antifungal effect. NO increases mucociliary clearance by upregulating ciliary motility; an association between low levels of NO and impaired mucociliary transport has been established [23,24]. Importantly, nitric oxide can display a pro- or anti-inflammatory effect conditioned by the type and phase of airway inflammation, its local concentration, and the individual response [25].…”
Section: Discussionmentioning
confidence: 99%
“…The low levels of nasal NO in PCD may be due to several possible reasons – primarily, impaired NO synthesis. As already mentioned, it has been shown that the application of NO donors into the human nasal mucosa stimulates ciliary beat [98], and that low NO levels result in an impaired muco-ciliary function in the upper airways [19,99]. In fact, Loukides et al [100] demonstrated that in patients with PCD, L -arginine (a substrate for NO production) induced an increase in nasal NO levels, as well as improved ciliary beating frequency and nasal mucociliary clearance.…”
Section: No In Primary Ciliary Dyskinesiamentioning
confidence: 99%
“…[4][5][6][7][8] Based on the recent advances in single-cell RNA-sequencing it became evident that more than one BC type exists in the airways and BC signature varies in different organs. [14][15][16][17] In the human upper airways nitric oxide released in response to taste receptor (TasR) stimulation increases ciliary beat, [18][19][20][21] but there is no proof that the same mechanism operates in the lower airways or additional mechanisms are influencing MC. 7,12 Yet, it remains elusive if these cells indeed synthesize and release ACh.…”
Section: Introductionmentioning
confidence: 99%
“…13 Cholinergic signaling is important for several innate immune processes in the airways, including MC. [14][15][16][17] In the human upper airways nitric oxide released in response to taste receptor (TasR) stimulation increases ciliary beat, [18][19][20][21] but there is no proof that the same mechanism operates in the lower airways or additional mechanisms are influencing MC. However, cholinergic signaling is important for other innate immune responses in the upper airways, since activation of solitary chemosensory cells (SCC) leads to cholinergic-mediated neurogenic inflammation in the nose.…”
Section: Introductionmentioning
confidence: 99%